2021
DOI: 10.3389/fpsyg.2021.621742
|View full text |Cite
|
Sign up to set email alerts
|

A Subtle Profile With a Significant Impact: Language and Communication Difficulties for Autistic Females Without Intellectual Disability

Abstract: The presentation of autism in females is poorly understood, which is thought to contribute to missed or later- age diagnosis, especially for those without intellectual disability. Dedicated research into social and behavioral differences has indicated a specific female phenotype of autism. However, less has been done to explore language and communication profiles, despite known sex/gender differences in typically developing populations. This article provides a synthesis of recent work from this small but emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 73 publications
(118 reference statements)
1
8
0
Order By: Relevance
“…These authors did not find any statistical differences in grammar skills (and basic vocabulary) between Ms and Fs. Moreover, in a recent paper, Sturrock et al [37] provide a synthesis of recent studies investigating language and communication difficulties in autistic Fs without intellectual disability. The authors found that autistic Fs appeared to perform below typically developing Fs on measures of pragmatics, semantics, and above sentence-level structural language; however, vocabulary and basic grammar (receptive and expressive) appeared to be unaffected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors did not find any statistical differences in grammar skills (and basic vocabulary) between Ms and Fs. Moreover, in a recent paper, Sturrock et al [37] provide a synthesis of recent studies investigating language and communication difficulties in autistic Fs without intellectual disability. The authors found that autistic Fs appeared to perform below typically developing Fs on measures of pragmatics, semantics, and above sentence-level structural language; however, vocabulary and basic grammar (receptive and expressive) appeared to be unaffected.…”
Section: Discussionmentioning
confidence: 99%
“…The abovementioned studies focused more on social and pragmatic domains rather than on basic structural language and identified pragmatic and associated higher-level structural language skills as areas of difference between the M and F phenotypes of ASD [29,30,33]. Indeed, S/G differences appear to exist mainly in domains where the meaning of structural language is mediated by social context, inference, language of emotion and internal state, and pragmatic behaviors in discourse and narratives [37].…”
Section: Introductionmentioning
confidence: 99%
“…This forms an important direction for future research. Further, given that autistic females have a different profile of strengths than autistic males (e.g., Sturrock et al, 2021), another limitation concerns the differences in gender distribution between the sub-study and the main study samples. This study was also limited by a relatively small sample size and small effect sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Further, precocious puberty has been associated with ASD in girls [27]. Additionally, it is more di cult to diagnose social impairments in girls due to the increased ability to camou age (i.e., perform socially 'appropriate' behaviors) [28,29] and enhanced verbal function compared to boys with ASD [30]. This camou aging (e.g., masking) ability can persist into adulthood [31], increasing the likelihood of women living with ASD to not receive appropriate diagnosis and supportive care.…”
Section: Introductionmentioning
confidence: 99%